Trajetórias da reclusão: uma análise das imagens de liberdade e privação entre adolescentes de Sinop, MT - Carvalho, Sandra Pereira de (Universidade do Vale do Rio dos Sinos, 2011)
This study is dedicated to knowing the trajectory of deprivation of liberty of some adolescents in the city of Sinop/MT, which were transferred to the Center of Socio Education of Cuiabá/MT. The study discusses some of the processes experienced by the marginalized classes of society, and is the guiding elements of research, space and reality of social phenomena that pervade the actors interviewed. To know this reality is a basic requirement in order to understand their values, their culture and subjectivity, in the spaces of social inclusion. The research is developed through narratives and interviews of adolescents in situations of deprivation of liberty, establishing the relationship between text and context explored. To do so, begins with the apprehension of the scene where he gave his internment (Sinop/MT) previous to the transference to Cuiabá / MT. Later, we discussed the trajectory of deprivation of liberty and its challenges in the context of the Center of Socio Education. The research focuses on theories that include discussions on the themes: equality and liberty, liberty and autonomy, relationships of equality and negative liberty and/or positive; deprivation of liberty and social vulnerability. Through the use of interviews, the study points out their careers, to discuss how these adolescents and society construct a path of possibilities and impossibilities, ahead the constitution of public politics of processes for social inclusion.
Keywords: Trajetórias de reclusão; Adolescentes; Vulnerabilidade social; Liberdade e autonomia; Políticas públicas; Trajectories of reclusion; Adolescents; Social vulnerability; Liberty and autonomy; Public politics; ACCNPQ::Ciências Humanas::Sociologia